The hunger games: sensing host arginine is essential for Leishmania parasite virulence - Goldman-Pinkovich, Adele; Kannan, Sriram; Nitzan-Koren, Roni; Puri, Madhu; Bar-Avraham, Yael; Mcdonald, Jacqueline A; Sur, Aakash; Wen-Wei, Zhang; Matlashewski, Greg; Madhubala, Rentala; Michaeli, Shulamit; Myler, Peter J; et al. (bioRxiv, 2019)
Abstract Arginine homeostasis in lysosomes is critical for growth and metabolism of mammalian cells. They employ a specific sensor (SLC38A9) that monitors intra-lysosome arginine sufficiency and subsequently up-regulates cellular mTORC1 activity. Lysosomes of macrophages (phagolysosomes) are the niche where the parasitic protozoan Leishmania resides and causes important human disease. Several years ago, we discovered that upon arginine starvation, cultured Leishmania parasites promptly activate a MAPK2-mediated Arginine Deprivation Response (ADR) pathway, resulting in up-regulation of the Leishmania arginine transporter (AAP3), as well as a small group of other transporters. Significantly, ADR is also activated during macrophage infection, implying that the intracellular parasite actively depletes arginine within the host phagolysosome, likely to prevent mTORC1 activation and enhance intracellular development. We hypothesize that ADR-mediated up-regulation of AAP3 activity is necessary to withstand the resultant arginine starvation. Both copies of the AAP3 genes are located (in tandem) on a tetrasomic chromosome (chr31), but only one (AAP3.2) is responsive to arginine deprivation. CRISPR/Cas9-mediated disruption of the AAP3 locus yielded mutants that retain a basal level of arginine transport (mediated by AAP3.1), but lack a functional copy of AAP3.2 and are therefore not responsive to arginine starvation. While these mutants grow normally in culture as promastigotes, they were impaired in their ability to develop inside THP1 macrophages grown under physiological concentrations of arginine (0.1 mM). However, flooding the macrophage growth medium with arginine (1.5 mM) restored parasite infectivity and intracellular growth to that of wild type. The results indicate that inside the host macrophage, Leishmania must overcome the arginine “Hunger Games” by up-regulating transport of arginine via the ADR. Furthermore, the AAP3.2 mutants were ~70-80% less virulent in Balb/C mice, showing, for the first time, that the ability to monitor and respond to changes in host metabolite levels is essential for pathogenesis.